A systematic study of the stability, electronic and optical properties of beryllium and nitrogen co-doped graphene. (April 2018) - Olaniyan, O.; Maphasha, R.E.; Madito, M.J.; Khaleed, A.A.; Igumbor, E.; Manyala, N.
Abstract: Ab-initio calculations within the framework of density functional theory (DFT) have been performed to study the stability, electronic and optical properties of Be and N singly doped and co-doped graphene. The effect of the dopants concentration and isomerization on the electronic and the optical properties of these systems have been studied. It has been found that Be-N is more stable than Be-doped graphene. The transition from semi-metallicity as in the case of pristine graphene to semi-conducting of graphene doped separately with Be, N and pairs of Be-N has been observed. Both Be and Be-N co-doped graphene exhibit p-type character. Moreover, the size of the band-gap observed in these aforementioned systems increases with the impurity concentrations. All the systems investigated are transparent within the frequency interval of 7.0–10 eV for parallel electromagnetic polarization. In general, we observed that the optical properties of the doped systems studied, respond to doping concentration differently across the electromagnetic spectrum with respect to the polarization field vectors. The results of our study demonstrate Be-N co-doped graphene to be a more realistic p-type semiconductor than Be-doped graphene and the band-gap can be tailored to meet the requirements of specific applications in nanoelectronic and optoelectronic devices. Graphical abstract: Image 1